Numerical methods for engineers with personal computer applications - Chapra, Steven C.; Canale, Raymond P. (McGraw-Hil Educationl, 2015)
Presenting a fresh approach which opens each part with sections called "Motivation," "Mathematical Background," and "Orientation", this book intends to deepen our understanding of what has been learned and provides a peek into more advanced methods. Numerous new or revised problems are drawn from actual engineering practice